Digitized Industrial Work: Requirements, Opportunities, and Problems of Competence Development - Baethge-Kinsky, Volker (Frontiers in Sociology, 2020)
German companies have been affected by a new wave of digitalization during the past years, and this has led to responses both in the way production is organized and in the goals of German industrial policy. The coordinated response is widely referred to as "Industry 4.0" and is intended to support German industries in the increasingly fierce competition for global leadership in manufacturing. Simultaneously, a social science debate about changes in work and employee training began and continues to this day. Far-reaching predictions of fundamental change circulate. Other issues include the needs and opportunities of firm-based competence development at work as well as the role and the uses of digital media. In recent years, more empirical studies have become available for clarifying open questions, and this paper presents three main results from one such study based on case investigations in ten German industrial firms. First, digitalization does not change industrial production work radically. There is no general trend of upskilling, downgrading, or reskilling. A moderate trend favoring upgrading is observable, however. Thus, traditional workforce competences are not becoming "obsolete." Rather, in the context of automation, they are being complemented by other skills including new technical qualifications in information technology as well as the ability to take a more theoretical approach to problem-solving in process optimization. Second, our results confirm more cautious assessments of the need for accelerated continuing vocational training. They also make it clear that the potential for increased learning opportunities in digital work and for the increased use of digital media in continuing vocational training has been overestimated. Learning opportunities seem to decrease rather than increase with digital work. Moreover, the use of digital media in continuing vocational training is limited due to organizational, financial, and cultural constraints and due to the lack of knowledge about the effectiveness of digital learning environments. Third, a number of organizational measures are needed to manage change. One measure would be to integrate new skill requirements into a binding institutional curriculum for education and training. Another measure would be to make on-the-job learning opportunities a central aspect of how work is organized.